A critical review of production factors that influ-ence egg quality traits - John-Jaja, Sylvia; Abdullah, Abdur-Rahman; Nwokolo, Samuel (International Journal of Scientific World, 2017)
The global poultry industry has experienced significant changes in the methods used to harvest and process the fresh egg over the past century. Applications of animal genetics and breeding have significantly increased in line speed for poultry operation. In this study aims at reviewing production factors that influence egg quality traits across the globe. The production factors so far utilized were classified into three main categories and presented based on their influencing capacity. For this purpose, two types of search criteria to find publications relevant to the scope of this review were employed. The first type was an automatic search performed on the following publishers' databases: ScienceDirect, Google's scholar, researcher gates, academia. The second type was a manual search on conferences, recent theses and dissertation that have not been published in journals from numerous Babcock University. Generally, 23 publications were reported for the breed; 17 for housing, and 19 for age of the breed after excluding studies that do not focus explicitly on breed, housing and age of the bird as production factors that influenced egg quality traits out of 183 potential relevant articles identified from January 2001 to December 2016. Thus, this review would provide animal genetics and breeding researchers in terms of identifying the most potent breed, adequate housing system and precise age for optimum production of birds with high quality.